Identifikasi Karakter Morfologis Asam Gelugur (Garcinia atroviridis Griff. ex T. Anders) di Beberapa Kabupaten Sumatera Utara - Budiman Febrian Halomoan Sidabutar; Eva Sartini Bayu; Mbue Kata Bangun (Jurnal Agroekoteknologi, 2018)
This reserach aimed to identify the morphological chracteristics and phylogenetic relationship of asam gelugur in three North Sumatera district. The research was done at Deli Serdang district, Langkat district and Serdang Berdagai district in Mei to September 2016 with survey method using asam gelugur descriptor of IPGRI. Sampling technique using accidental sampling. Parameters observed were tree height, trunk height, trunk circumference, trunk surface, crown shape, young leaf colour, mature leaf colour, leaf blade size (lenght and widht), leaf blade shape, leaf base shape, leaf apex shape, leaf blade margin, leaf venation appearance, flower size, position of flowers, sepal colour, petal colour, fruit shape, number of fruit segments, fruit diameters, fruit weight, fruit size, fruit skin thickness, mature fruit colour, seed lenght, seed widht, number of seeds per fruit, seed shape, seed coat colour. This result of research showed that in tree North Sumatera district there were 21 accession of asam gelugur been identified. The result of morphologycal characteristics for crown shape (pyramidal and elliptic), trunk surface (smooth, rough, very rough), leaf shape (elliptic, oblong, lanceolate), flower shape (female flower and hermaphrodite flower), fruit shape (round, flattened, ovoid).   Keywords : garcinia atroviridis, identification, morphologycal-characteristics